(untitled) (Research, Society and Development, 2023)
Medicinal plants and phytotherapy are used as complementary or alternative treatments for the management of different diseases. Within this context, herbal medicines arise and should be obtained with the exclusive use of active plant raw materials, whose safety and efficacy are based on clinical evidence. However, easy access in community pharmacies favors self-medication. The objective of the research was to identify the main herbal medicines dispensed in community pharmacies, to support pharmacists in promoting the rational use of medicines. This was an integrative review of the literature through the databases: Virtual Health Library® (BVS), Scientific Electronic Library Online® (Scielo) and Google Scholar®. The Descriptors in Health Sciences (DeCS) were used: Phytotherapy, Herbal Medicines, Community Pharmacy. 13 articles were selected to make up the discussion stage. Passiflora Incarnata L was the most mentioned plant species in the studies, followed by Ginkgo biloba and Valeriana officinalis. Such medications are indicated against disorders in the Central Nervous System (CNS), and are often the first choice in the treatment of anxiety and insomnia, and use guidelines are required by qualified professionals. In view of the above, it is concluded that herbal medicines are obtained exclusively on the basis of active plant raw materials, characterized both by the efficacy and low risks of their use. However, it is possible to observe potential toxicity when used without guidance. Thus, pharmacists must present knowledge about these drugs to promote rational use at the time of dispensing, achieving the objectives of pharmaceutical care.